PENGARUH KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM - Muhammad Ali Fikri Hakami (Universitas muhammadiyah malang, 2014)
The research aim is to analyze the effect of dividend policy on company’s stock price. The analysis used Distributed-Lag Regression with Alt and Timbergen Method. The result shows that devident policy has lower contribution on stock price. Dividend on the t-2 period has a significant influence on the stock’s price, but on the t-1 period, and t-3 there were no significant effect. The finding indicates that dividend policy has a significant effet on stock price. it means the more dividend increase, stock’s price will increase high. Keyword: Dividend Policy, Stock Price, Timbergen Method.